Climatic response of radial growth of Larix cajanderi in the Northern and Central Yakutia - K. I. Khotcinskaia; O. V. Sergeeva; A. V. Kirdyanov; A. N. Nikolaev; K. V. Akulinina; N. N. Koshurnikova; A. I. Kolmogorov; A. Arzac; К. И. Хоцинская; О. В. Сергеева; А. В. Кирдянов; А Н. Николаев; et al. (Lomonosov Moscow State University, School of Biology, 2024)
Warming trends in high latitudes will lead to changes in the thermo-hydrological regime of permafrost soils, affecting the structure and functioning of northern ecosystems. The study of radial tree growth response to current environmental conditions is commonly used to understand the future reaction of trees. This study evaluates the response of four Cajander larch (Larix cajanderi Mayr) sites in the continuous permafrost region to different environmental conditions in Northern and Central Yakutia (Republic of Sakha). Correlation coefficients between tree-ring width indexes and climate parameters were calculated over the 1966–2021 period. The results showed that air temperature is the main factor limiting the radial tree growth in all the sites (mainly June temperature; r = 0,38–0,41; p < 0,01). However, the timing and intensity of the temperature sensitivity increases with the latitude. The most sensitive to climate woody plants grow in the northern part of the study region where growing season is rather short. Running correlations showed a general decreasing trend in intensity of the temperature response in radial growth chronologies. Probably it is linked to the increase in summer temperatures in recent decades, thus highlighting the ecological plasticity of the larch trees. These results can help to assess changes in the productivity of the forest ecosystems in particular regions of boreal zone. Повышение температуры в высоких широтах приведет к изменению водного баланса и термического режима многолетнемерзлых почв, что повлияет на структуру и функционирование растительных сообществ северных биогеоценозов. Изучение отклика радиального прироста деревьев на текущие изменения среды и климата является одним из методов для понимания реакции отдельных компонентов растительных сообществ в будущем. В работе представлены результаты дендроклиматического анализа деревьев лиственницы Каяндера (Larix cajanderi Mayr), произрастающих в зоне сплошного распространения многолетней мерзлоты на четырех участках с ...